The evolution of International business 1800-1945. Volume V : Private investment in India, 1900-1939 - Bagchi, Amiya Kumar (London ; New York : Routledge, 2000)
The economic policy of the Government of India. The record of aggregate private industrial investment in India, 1900-1939. Land and the supply of raw materials. The supply of raw materials. The supply of unskilled labour. The supply of capital and entrepreneurship...
Keywords: Economics; Investments; Industries; Investments -- India; Industries -- India; India -- Economic policy